Characterization of a genomic clone for rat seminal vesicle secretory protein IV. - Kandala, J C (1983)
The entire coding region for rat seminal vesicle secretory protein IV was obtained on a 3.5 kb Eco RI fragment isolated from a genomic library in lambda Charon 4A. The coding sequence for SVS IV message is interrupted twice by introns. The first lies just downstream from the juncture of the 21 amino acid secretory signal peptide with the start of the mature protein, and the second lies in the 3'-nontranslated region. The major transcriptional start site was mapped by primer extention and is 22 nucleotides upstream from the translational initiation codon. S1 protection experiments indicated additional minor transcriptional starts about 27 and 50 nucleotides further upstream from the major cap site. The entire transcriptional unit comprises about 1740 nucleotides. The SVS IV gene does not belong to an obvious gene family, and it is conserved in mice and guinea pigs.